The synthesis of the β-glucosidase enzyme in the transgenic rice seeds for replacement therapy of the heritable Gaucher disease - Zlata, Zlata (Anali PAZU, 2022)
Production of active ingredients for pharmaceuticals, especially vaccines with transgenic crops, began 25 years ago. Due to certain advantages of the synthesis of active transgenic crops ingredients, in comparison with the current production, the optimized transformation expression systems and their application are gaining ground. Until now, the focus has been on sourcing agents for preventing and treating a variety of infectious human and animal diseases. In recent years, there is an increasing number of cases including the acquiring of recombinant proteins for the treatment of autoimmune and genetic diseases, including the very rare Gaucher disease (lack an enzyme glucocerebrosidase), which can be treated with replacement enzyme β-glucosidase. Transgenic rice successfully synthesized and imposes β-glucosidase in the endosperm during the period of formation and maturation of seeds.